ANALISIS SWOT PENYELENGGARAAN DIKLAT ONLINE TIK GURU - Eni Susilawati (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2016)
Information and Communication Technology (ICT) has been highly demanded in education and Pustekkom (Center of ICT for Education of Indonesia Ministry of Education and Culture) has implemented online ICT training for teachers. In relation to it, the purpose of this research was to analyze the implementation of ICT online training and to get feedback for strategy in improving the quality of ICT online training implementation. The study was conducted with qualitative methods using SWOT matrix approach to formulate a strategy to improve the quality of education and online training. Sample was taken from the ICT online training participants in 15 locations held by Pustekkom in 2015. The collecting data using a list of open questions and observations were limited in accordance with the purpose of research.The result shows that the result of the analysis of ICT online training for teachers in 2015 can be used as input to improve the quality of implementation of the ICT online training for participants, organizer, and stakeholders. It also reveals that the success of the training are determined by external and internal factors(Strength, Weakness Opportunity and Threats). In conclusion, the SWOT analysis gives four alternative formulation strategies, namely, Opportunities-Strength (SO), Weaknesses-Opportunities (WO), Strength-Threats (ST), and Weaknesses-Threat (WT) covering improvement of the quality of application, training package (selection process, curriculum, implementation), infrastructure, human resource (participants, organizers), and commitment of the relevant stakeholders. ABSTRAKIntegrasi teknologi dan Informasi (TIK) dalam pembelajaran telah menjadi sebuah tuntutan dan Pusat Teknologi Informasi dan Komunikasi Pendidikan dan Kebudayaan sebagai salah satu stakeholder pemanfaatan TIK dalam pendidikan telah menyelenggarakan diklat online TIK bagi para guru. Berkaitan dengan hal tersebut, penelitian ini bertujuan menganalisis pelaksanaan pendidikan dan pelatihan (diklat) online TIK bagi guru dan mendapatkan masukan strategi dalam peningkatan kualitas penyelengggaraan diklat online TIK pada tahun berikutnya. Penelitian dilakukan dengan metode kualitatif, dengan menggunakan pendekatan matrik SWOT untuk merumuskan strategi peningkatan kualitas penyelenggaraan diklat online. Obyek penelitian diambil dari perwakilan peserta diklat online TIK di 15 lokasi yang diselenggarakan oleh Pustekkom pada tahun 2015. Pengumpulan data menggunakan daftar pertanyaan terbuka dan observasi terbatas sesuai dengan tujuan penelitian. Hasil penelitian menunjukkan bahwa hasil analisis SWOT diklat online TIK guru tahun 2015 dapat dijadikan masukan dalam peningkatan kualitas penyelenggaraan diklat online TIK bagi peserta diklat, penyelenggara, dan stakeholder terkait dan keberhasilan diklat online TIK bagi guru ditentukan oleh faktor eksternal (peluang dan ancaman) dan internal (kekuatan dan kelemahan). Penelitian ini menyimpulkan bahwa dari hasil analisis SWOT diperoleh empat rumusan alternatif strategi yaitu Strategi Strength–Opportunities (SO), Weaknesses–Opportunities(WO), Strength–Threats(ST), dan Weaknesses–Threat (WT) yang mencakup peningkatan kualitas dari sisi aplikasi, kemasan diklat(proses seleksi, kurikulum, pelaksanaan), sarana prasarana, SDM(peserta, penyelenggara ), dan komitmen stakeholder yang terkait.